Enhanced thermal performance of tubular heat exchanger using triangular wing vortex generator. Issue 1 (31st December 2022) - Sharma, Vansh Ratna; S, Sai Sankalp; N, Madhwesh; M S, Manjunath
Abstract: Enhancement of heat transfer for turbulent flow in a circular tube heat exchanger using triangular wing v ortex generators (TWVG) is presented using Computational Fluid Dynamics methodology. A detailed parametric analysis is carried out to evaluate the impact of non-dimensional base width (0.059–0.216), non-dimensional height (0.039–0.314) and different flow attack angle of TWVG (α = 22.5°, 45°, 67.5°, 90°, 112.5° and 135°) for Re = 6000–18, 000. The results show that the TWVG provides considerable heat transfer improvement through two mechanisms such as flow impingement effect on the upstream side and vortex formation on the downstream side. The heat transfer is found to decrease with increasing flow attack angle. However, the friction factor is found to increase from α = 22.5° to α = 90° and drops for all α > 90° due to increased streamlined orientation of vortex generator to the air stream. Longitudinal vortices are formed for α = 22.5°, whereas transverse vortices are generated for all other flow attack angles used in the analysis which are found to have lower flow mixing effect as well as lower coverage of tube wall region. Greater height and base width of TWVG provides greater heat transfer and friction factor enhancement. The maximum enhancement in Nusselt number and friction factor is in the range of 2.61–2.96 and 6.54–8.1 respectively for b/D = 0.216 and h/D = 0.314. The maximum thermal enhancement factor is produced by the configuration having h/D = 0.235 and b/D = 0.059 and has a range of 1.34–1.63.